Optimization of argon-air DBD plasma-assisted grafting of polyacrylic acid on electrospun POSS-PCUU. (July 2023) - Zakeri, Ziba; Salehi, Roya; Mahkam, Mehrdad; Siahpoush, Vahid; Rahbarghazi, Reza; Sokullu, Emel; Abbasi, Farhang
Abstract: It is accepted that significant interfacial reactions take place in engineered tissues between biomaterial surfaces and the host's tissue in the body. The lack of appropriate functional groups limits long-term biocompatibility and successful biological response of biomaterials. Therefore, the cell-biomaterial affinity should be increased by functional groups grafting to the surface of biomaterials which provide the basic properties of the desired tissue. For the first time in this study, PAAc grafting was performed using two-step argon-air DBD plasma at atmospheric pressure in a few seconds of exposure time, to modify the surface of POSS-PCUU nanofibers to selectively increase their superficial properties while maintaining the required mechanical properties. The Response Surface Methodology was used for experimental design to optimize the operating conditions of carboxylic acid grafting at the electrospun POSS-PCUU surface. Nanofiber surface modification was confirmed using ATR-FTIR, FE-SEM, AFM, WCA, and tensile test. The grafting of PAAc to the nanofiber surface was proved by the presence of a broad hydroxyl band in ATR-FTIR spectrum, the morphological changes observed in the SEM and AFM images, and the reduction of the water contact angle. The stress-strain behavior at the optimum point also showed an acceptable reduction in tensile strength. Furthermore, the effects of two variables, plasma processing time and plasma copolymerization time were optimized and investigated using the CCD method at five levels of carboxylic acid grafting density. The grafting of PAAc onto the nanofiber surface (73.69 ± 2.1 μg/cm 2 ) produced at reaction conditions displayed great agreement with the predicted results by the model. Results showed that the modified PAAc-POSS-PCUU nanofibers will be a desirable surface for the immobilization of various ECM proteins with high potential in small-diameter vascular graft applications. Highlights: Surface of POSS-PCUU nanofibers was modified by PAAc grafting using two-step argon-air DBD plasma at atmospheric pressure in a few seconds of exposure time. The effects of two variables, plasma processing time and plasma copolymerization time were optimized and investigated using the CCD method at five levels of carboxylic acid grafting density. As a result of PAAc bonding to the inert surface of POSS-PCUU nanofibers as well as the formation of oxidized crosslink structures, such as alkyl peroxide structures, surface energy, and surface hydrophilicity increased with the increasing density of carboxyl groups at the nanofiber surface. By grafting of PAAc onto the POSS-PCUU nanofibers with surface two-stage plasma processing caused to increase in roughness of PAAc-POSS-PCUU nanofibers compared to unprocessed POSS-PCUU fibers. This increase in volume relative to the area provides greater hydrophilicity and stronger surface interactions at the acrylic acid grafted nanofiber surfaces.